New theropod remains and implications for megaraptorid diversity in the Winton Formation (lower Upper Cretaceous), Queensland, Australia - Matt A. White; Phil R. Bell; Stephen F. Poropat; Adele H. Pentland; Samantha L. Rigby; Alex G. Cook; Trish Sloan; David A. Elliott (Royal Society Open Science, 2020)
The holotype specimen of the megaraptorid Australovenator wintonensis, from the Upper Cretaceous Winton Formation (Rolling Downs Group, Eromanga Basin) of central Queensland, is the most complete non-avian theropod found in Australia to date. In fact, the holotype of A. wintonensis and isolated megaraptorid teeth (possibly referable to Australovenator) constitute the only theropod body fossils reported from the Winton Formation. Herein, we describe a new fragmentary megaraptorid specimen from the Winton Formation, found near the type locality of A. wintonensis. The new specimen comprises parts of two vertebrae, two metatarsals, a pedal phalanx and multiple unidentifiable bone fragments. Although the new megaraptorid specimen is poorly preserved, it includes the only megaraptorid vertebrae known from Queensland. The presence of pleurocoels and highly pneumatic caudal centra with camerate and camellate internal structures permit the assignment of these remains to Megaraptora gen. et sp. indet. A morphological comparison revealed that the distal end of metatarsal II and the partial pedal phalanx II-1 of the new specimen are morphologically divergent from Australovenator. This might indicate the presence of a second megaraptorid taxon in the Winton Formation, or possibly intraspecific variation.